Saliva microbiome changes in thyroid cancer and thyroid nodules patients - Jiao, Junjun; Zheng, Youli; Zhang, Qingyu; Xia, Degeng; Zhang, Li; Ma, Ning (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: Thyroid disease has been reported to associate with gut microbiota, but the effects of thyroid cancer and thyroid nodules on the oral microbiota are still largely unknown. This study aimed to identify the variation in salivary microbiota and their potential association with thyroid cancer and thyroid nodules. Methods: We used 16S rRNA high-throughput sequencing to examine the salivary microbiota of thyroid cancer patients (n =14), thyroid nodules patients (n =9), and healthy controls (n= 15). Results: The alpha-diversity indices Chao1 and ACE were found to be relatively higher in patients with thyroid cancer and thyroid nodules compared to healthy controls. The beta diversity in both the thyroid cancer and thyroid nodules groups was divergent from the healthy control group. The genera Alloprevotella, Anaeroglobus, Acinetobacter, unclassified Bacteroidales, and unclassified Cyanobacteriales were significantly enriched in the thyroid cancer group compared with the healthy control group. In contrast, the microbiome of the healthy controls was mainly composed of the genera Haemophilus, Lautropia, Allorhizobium Neorhizobium Pararhizobium Rhizobium, Escherichia Shigella, and unclassified Rhodobacteraceae. The thyroid nodules group was dominated by genre uncultured Candidatus Saccharibacteria bacterium, unclassified Clostridiales bacterium feline oral taxon 148, Treponema, unclassified Prevotellaceae, Mobiluncus, Acholeplasma. In contrast, the genera unclassified Rhodobacteraceae and Aggregatibacter dominated the healthy control group. The study also found that clinical indicators were correlated with the saliva microbiome. Conclusion: The salivary microbiota variation may be connected with thyroid cancer and thyroid nodules.